Endocannabinoid metabolism and peroxisome proliferator-activated receptor signalling - Dionisi, Mauro (2010)
The fatty acid amides (FAAs) family includes endocannabinoids, such as anandamide, as well as endocannabinoid-like molecules, such as N-palmitoylethanolamine (PEA) and N-oleoylethanolamine (OEA). Members of the FAA family show agonist activity at transmitter-gated channels (TRPV1), as well as peroxisome poliferator-activated receptors (PPARs). Given that FAAs appear to be hydrolysed principally through the action of the enzyme fatty acid amide hydrolase, inhibition of FAAH should lead to accumulation of a variety of FAAs. Therefore, in this study it was investigated whether pharmacological inhibition of FAAH could influence PPAR activity in SH-SY5Y human neuroblastoma cells or HeLa human cervical carcinoma cells. FAAH activity was assessed by monitoring liberation of [3H]-ethanolamine from labelled anandamide. FAAH protein and RNA expression were measured by immunoblotting and qRT-PCR respectively. Endocannabinoid levels were measured by LC-MS/MS. In order to evaluate PPAR activation, a PPRE-linked luciferase construct was co-transfected with expression plasmids for either PPAR α, β or γ. Binding to PPAR receptors was assessed with a competitor displacement assay (Invitrogen). In intact SH-SY5Y cells, sustained FAAH inhibition by URB597 (~75 %) led to accumulation of AEA, 2AG and PEA, but not OEA. Treatment with URB597, OL135 or PF750, three structurally and functionally distinct FAAH inhibitors, induced activation of endogenously expressed PPARs, while no activation was observed in FAAH-1 negative HeLa cells. Furthermore, exposure to URB597, OL135 or PF750 led to activation of over-expressed PPARs in SH-SY5Y cells. To rule out direct activation of PPARs by the FAAH inhibitors, cell-free binding assays showed that URB597, OL135 and PF750 could not bind to PPARα, PPARβ or PPARγ. Surprisingly, treatment with URB597 in HeLa cells led to intracellular accumulation of PEA but not AEA, OEA or 2AG. This might be due to inhibition of either FAAH-2 or NAAA, both of which are expressed in HeLa cells. Moreover, the presence of either URB597 or OL135 led to activation of PPARγ receptors over-expressed in HeLa cells. In conclusion, data in this study showed activation of PPAR nuclear receptors in vitro by inhibition of FAAH activity and subsequent augmentation of endocannabinoid tone. These data suggest that, at least in a model setup, it is possible to modulate the endocannabinoid tone without any previous external stimulus of their synthesis and trigger a functional effect.